USAHA MENINGKATKAN KOMITMEN DAN KINERJA ASN PEMKOT KUPANG MELALUI MOTIVASI KERJA - Jefirstson Richset Riwukore (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of community service activities (PkM) is to educate and train State Civil Apparatus (ASN) to have knowledge and skills in evaluating and reconstructing efforts to increase ASN commitment and performance through motivation. Focus group discussions (FGD) and workshops are technical tools to implement this PkM. The main partner of this PkM activity is the ASN of the Kupang City Government which is determined by purposive sampling and quota sampling techniques. PkM participants were 28 people. The SWOT analysis is the basis for PkM education and training to participants. The success of this PkM activity is that participants are educated and have the knowledge and skills in evaluating and reconstructing strategies to increase commitment and performance through motivation. The reconstruction of the strategy is to strengthen the understanding base of the state civil apparatus through continuous knowledge management related to the principles of basic duties as government employees, considering compensation in terms of increasing commitment and performance by cutting the budget for activities that are disproportionate and dual functions so that it can be transferred to employee compensation, and enforced an integrity pact-based performance that will discipline employees at work.